2018
DOI: 10.1177/0146645318756837
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the integrated approach in different types of exposure scenarios

Abstract: The International Commission on Radiological Protection (ICRP) recognises three types of exposure situations: planned, existing, and emergency. In all three situations, the release of radionuclides into the natural environment leads to exposures of non-human biota, as well as the potential for exposures of the public. This paper describes how the key principles of the ICRP system of radiological protection apply to non-human biota and members of the public in each of these exposure situations. Current work in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Johansen et al 2019measured radionuclide levels in tissues from different biota, and showed that those coming into contact with the contaminated island soils typically had higher levels of radionuclide accumulation. The need to consider aspects such as these in the context of existing exposure situations was discussed further in Copplestone et al (2017).…”
Section: Applying the Dcrls In Emergency And Existing Exposure Situatmentioning
confidence: 99%
“…Johansen et al 2019measured radionuclide levels in tissues from different biota, and showed that those coming into contact with the contaminated island soils typically had higher levels of radionuclide accumulation. The need to consider aspects such as these in the context of existing exposure situations was discussed further in Copplestone et al (2017).…”
Section: Applying the Dcrls In Emergency And Existing Exposure Situatmentioning
confidence: 99%